An extensive study of hydrogen-induced cracking susceptibility in an API X60 sour service pipeline steel. (23rd February 2016) - Mohtadi-Bonab, M.A.; Eskandari, M.; Rahman, K.M.M.; Ouellet, R.; Szpunar, J.A.
Abstract: API X60 sour service (X60SS) pipeline steel was subjected to electrochemical hydrogen-charging for different durations in order to evaluate its hydrogen-induced cracking (HIC) susceptibility. SEM observations of the hydrogen-charged specimens documented that no HIC cracks appeared at the cross section of steel, which is strong evidence of a high resistance to HIC. However, hydrogen-discharging results show that a considerable amount of hydrogen can enter the X60SS steel through its hydrogen traps. Moreover, a hydrogen-permeation test proved that the trapping behavior was almost identical at the center and surface layers of the cross section in this steel. However, the density of hydrogen traps at the center of the cross section was slightly higher than at the surface. Tensile and fatigue experiments were carried out in the air and in a hydrogen-charging environment using a newly constructed experimental setup. Tensile results show that the ductility dropped by 83% in the hydrogen-charging environment. Electron backscatter diffraction (EBSD) technique was used to analyze the HIC cracks in the X60SS steel. HIC cracks appeared after charging under tensile/fatigue tests. Therefore, high HIC-resistant steel showed susceptibility to HIC when charging and tensile stresses were applied simultaneously. The effects of different factors on HIC crack propagation such as micro-texture, type of grain boundaries, Kernel Average Misorientation (KAM), special coincidence site lattice (CSL) boundaries and recrystallization fraction, were discussed. Highlights: HIC susceptibility under external stress in X60SS pipeline steel was investigated. Hydrogen trapping behavior in X60SS pipeline steel was studied. SEM observations showed that HIC cracks were propagated in different directions. Effect of different microstructural parameters on hydrogen cracking was discussed.